Doktrin Gereja (Ekklesiologi): Sebuah Kajian Literatur - Dina Radina Singal; Eny Emelia Hewuni; Eka Andika Saputra; Sarmauli (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This article discusses how church doctrine relates to the church, where the church, as the body of Christ, is inseparable from the fundamental teachings of its faith and confession. Doctrine is a crucial foundation that supports church life. In the New Testament, the word ekklesia refers to